Information Technology Enterprise Architecture Planning in the National and Political Unity Agency “KESBANGPOL” of Salatiga City Using Enterprise Architecture Planning (EAP) - Chevin Robert Warint; Yani Rahardja; Melkior N. N Sitokdana (Politeknik Pertanian Negeri Samarinda, 2020)
The National and Political Unity Agency